2016
DOI: 10.1590/1983-1447.2016.03.57954
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes sociais da saúde e qualidade de vida de cuidadores de crianças com câncer

Abstract: the study sheds light on the influence of social determinants of health in the quality of life of caregivers of children with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
2
1
0
10
Order By: Relevance
“…According to the results found in this research study, most interviewed were children's mother, as in the study by Barbosa et al [8]. The age, low educational level, family income of a minimum wage and the source found in our study are in agreement with Rocha et al [10]. As in this research, additional studies have demonstrated a higher incidence of cancer in male children, such as those by Lopes et al [7], Barbosa et al [8] and Santos et al [6].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to the results found in this research study, most interviewed were children's mother, as in the study by Barbosa et al [8]. The age, low educational level, family income of a minimum wage and the source found in our study are in agreement with Rocha et al [10]. As in this research, additional studies have demonstrated a higher incidence of cancer in male children, such as those by Lopes et al [7], Barbosa et al [8] and Santos et al [6].…”
Section: Discussionsupporting
confidence: 91%
“…Dentistry, applied to pediatric oncology patients, plays a key role in keeping the overall health condition and, consequently, the quality of life of these children [9]. Poor oral health conditions are key etiologic factors to stomatologic and systemic complications, which can lead to patient's death [10].…”
Section: Introductionmentioning
confidence: 99%
“…La asociación significativa entre estado civil y comorbilidades con el componente de salud mental demostró que ser viudo y tener antecedentes mórbidos redujo el puntaje de las escalas de salud mental. La evidencia demuestra mejor calidad de vida a los cuidadores casados (15,19).…”
Section: Discussionunclassified
“…También, otras variables fueron relacionadas a la calidad de vida como número de morbilidades (17) y a la sobrecarga familiar como cuidadores jubilados, casados y con menor grado de escolaridad (18). En contrapartida, los cuidadores del sexo masculino, con alto nivel de educación, más jóvenes y casados, tienen una mejor calidad de vida (19).…”
unclassified
“…Contudo, é fundamental a conscientização de que uma cavidade bucal saudável influi positivamente no sucesso do tratamento médico 5 . As más condições de saúde bucal são fatores etiológicos determinantes não só das intercorrências estomatológicas, mas também das sistêmicas, podendo levar o paciente a óbito 25 .…”
Section: Discussionunclassified